2011
DOI: 10.1021/jp206077r
|View full text |Cite
|
Sign up to set email alerts
|

Mechanically Induced Phase Transformation of γ-Al2O3into α-Al2O3. Access to Structurally Disordered γ-Al2O3with a Controllable Amount of Pentacoordinated Al Sites

Abstract: One of the most important goals in materials science is the modification and design of solids to obtain functionalized materials with tailored properties. However, in many cases the structure–property relationships are unknown or turn out to be highly complex and difficult to bring under control. In the present paper we show how the atomic-scale structure of a technically important oxide can be modified by mechanical rather than by chemical treatment. We comprehensively investigated the phase transformation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
81
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 83 publications
(88 citation statements)
references
References 47 publications
6
81
1
Order By: Relevance
“…A systematic study of the influence of the various milling conditions on the phase transformation induced by mechanical action showed that the underlying mechanism is presumably similar to that reported for the thermally induced transformation [82,83], i.e. the growth of α-Al 2 O 3 starts from the unsaturated Al centers on the surface of a metastable γ-Al 2 O 3 crystallite and propagates into the inner regions [73]. Worth noting, when the initially formed penta-coordinated Al centers are immediately trapped after they have formed, e.g.…”
Section: Nanocrystalline Al 2 O 3 With Catalytically Active Penta-comentioning
confidence: 55%
See 4 more Smart Citations
“…A systematic study of the influence of the various milling conditions on the phase transformation induced by mechanical action showed that the underlying mechanism is presumably similar to that reported for the thermally induced transformation [82,83], i.e. the growth of α-Al 2 O 3 starts from the unsaturated Al centers on the surface of a metastable γ-Al 2 O 3 crystallite and propagates into the inner regions [73]. Worth noting, when the initially formed penta-coordinated Al centers are immediately trapped after they have formed, e.g.…”
Section: Nanocrystalline Al 2 O 3 With Catalytically Active Penta-comentioning
confidence: 55%
“…Reflections assigned to ZrO 2 originate from abrasion during milling in zirconia vials. The formation of crystalline α-Al 2 O 3 is hardly seen via X-ray diffraction; 27 Al MAS NMR helps identify amorphous phases formed, see (b) [73]. The 27 Al MAS NMR spectra of the starting material (shown at the bottom) reveal octahedrally and tetrahedrally coordinated Al cations as expected.…”
Section: Nanocrystalline Al 2 O 3 With Catalytically Active Penta-comentioning
confidence: 70%
See 3 more Smart Citations